Violência sexual contra crianças e adolescentes: uma experiência multiprofissional em um ambulatório pediátrico na Paraíba - Almeida, Zelândia Marques de (2020)
Sexual violence against children and teenagers is a multicausal phenomenon,closely related to cultural, economic and political determinants of modern society, a historical period when these social subjects were separated from the world of adults and assumed a new status; as well as with subjective and symbolic factors that permeate and forge interpersonal and intergenerational relationships. The research presented here aims to investigate the interfaces between childhood history, the phenomenon of sexual violence against children and teenagers and their confrontation by the Ambulatory of Assistance to Victims of Violence and Accidents - AMVIVA - a multiprofessional experience in the scope of public health, linked service the Arlinda Marques Pediatric Complex; emphasizing the profile of children, teenagers and families who accessed this specialized service and apprehensions, challenges and confrontations from the perspective of the professionals who make up the health team. Our study made use of a systematic review of the existing literature on the phenomenon, of data collected in the field, by consulting the institution's documents and conducting semi-structured interviews with professionals, from April to July 2019. We chose the dialectical historical materialism as the guiding theoretical focus, a choice based on the fact of the dialectical method places the phenomenon within a historical perspective, a product of the relationships that are established between the subjects. It is characterized by a qualitative-quantitative research, explanatory and descriptive related to the objectives, of an applied nature. The collected data were made explicit statistically and received analytical treatment using the content analysis technique. As results obtained through documentary research on children, teenagers and their families, it appears that 75.23% are female; 38.78% were in the age group between 7 and 11 years old at the time of care; 68.69% of the authors of the abusive acts have a parental bond with the victims, such as parents, stepparents, uncles, grandparents. As results obtained through the interviews carried out with the professionals, it appears that 100% are female; 75% had not previously been trained by the institution on issues related to coping with violence; 100% are not fully satisfied with working conditions, citing problems such as a small number of professionals; inadequate physical space and methodological difficulties of the team. In the case of the feelings aroused in the professionals on the occasion of attendance, the following attendance, fear that violence will affect them, blaming the victim, empathy, revolt, perplexity, malaise, among others. The socio-economic vulnerability of the family was shown to be the main factor that can culminate in the abuse and sexual exploitation of children and teenagers. With the results achieved, we point out the challenges of problematizing the phenomenon of sexual violence against children and teenagers, especially by the health sector, fostering their broader understanding, enabling its use to illuminate interventional projects to confront this type of violence and the development of future studies by the academic community.